STUDI KELAYAKAN PEMBANGUNAN INSTALASI JARINGAN PIPA AIR DENGAN METODE COST & BENEFIT ANALYSIS GUNA MEMINIMALKAN WAKTU MATERIAL HANDLING - Rengganis, Esa (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Production facility have a significant influence on production process. CV. Jokudo Kamsa got a problem on water filling on rotary drum, it takes 120 minutes on tanning process. It causes the facility is not enough for this process. So, we need to build pipe installation to reduce material handling time, especially on water fillingâs time. Feasibility study on pipe installation based on Benefit Cost Analysis Methode. We applied NPV, Payback Period and Return On Investment. Based on data tabulation we found Rp. 84,787,387,75 on NPV, 74,87 percent on ROI and 5.23 months on PP. And the most important thing we can reduce material handling time in 70 minutes on water filling with material handling cost as big as Rp. 139,804,9.